Problematizing the sociocultural production of nature: Considering settler colonialism in Confederation Park - Trudeau, Miho (The Canadian geographer, 2025)
This manuscript provides a viewpoint on issues of settler colonialism in relation to natural playground contexts. Reflections emerged while conducting a multi‐site study on natural playground development and usage in Calgary, Canada. One site was situated in a large urban green space, Confederation Park, and illustrated the materialization of green spaces as a settler‐colonial project . Ce manuscrit traite de l'aménagement des aires de jeux naturelles en milieu urbain et des enjeux associés, selon la perspective critique du colonialisme de peuplement. Cette réflexion a émergé d'une étude plus large sur le développement et l'utilisation des aires de jeux naturelles à Calgary, au Canada. Nous nous attardons ici sur un site localisé à l'intérieur d'un grand espace vert, soit le parc de la Confédération, lequel illustre bien la matérialisation des espaces verts en tant que projet colonial de peuplement . Settler‐colonial processes, such as the exclusion of Indigenous peoples and perspectives, are evident within the production and usage of North American wilderness areas and recreational green spaces. An analysis of a natural playground site in Calgary's Confederation Park reflected an erasure of Indigenous history and demonstrated the materialization of the site as a settler‐colonial project. Further research and practice‐based intervention on settler‐colonial green spaces, such as natural playgrounds, are required to reclaim and re‐story urban natural spaces.